If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3(5n + 6) = -93 Reorder the terms: -3(6 + 5n) = -93 (6 * -3 + 5n * -3) = -93 (-18 + -15n) = -93 Solving -18 + -15n = -93 Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '18' to each side of the equation. -18 + 18 + -15n = -93 + 18 Combine like terms: -18 + 18 = 0 0 + -15n = -93 + 18 -15n = -93 + 18 Combine like terms: -93 + 18 = -75 -15n = -75 Divide each side by '-15'. n = 5 Simplifying n = 5
| 29y=7(4y-3) | | -126=6(8x+3) | | x=7+4(y-3) | | -8a-3a=-22 | | 4n-3n=-7 | | 14+10A=44 | | -n+8n=21 | | (3x-1)(2x+4)=0 | | 33-7n=8(1-4n) | | 6x^2+1=12 | | -37-52=11z-85 | | 1-3v+1=2 | | x.2-8x-20=0 | | -3x-x=4 | | 21+7x=7(6x-7) | | 6m-7=8m+19 | | 3(x+4)=-2(x-7)-15 | | 7x=8x-6 | | 14-2x=2(7-x) | | 45x-36y=180 | | -37=-1+3(3n-3) | | x^3+x^2-56x=0 | | x^2+4x+17= | | -36=-1+3(3n-3) | | 5x+2=x+(2x-10) | | .6u+2=6 | | Y=16+.4(62) | | 2x^2+2x=-8x-12 | | 2x-1=-7x-1 | | -27-x^2=0 | | (-80)+33= | | 2(x+3)-4(x+9)=6(x+7) |